Gap Analysis of IT Governance in Supporting Integration of Organizational Universities (Case Study: University of General Achmad Yani Yogyakarta) - Amrina Friska Apriliana; Erma Suryani (IPTEK Journal of Proceedings Series, 2019)
Gap analysis is the first step in making universities have good IT governance. Gap analysis is a key requirement that can increase university success. More and more universities rely on information technology to manage universities. Information technology is an integral part of most universities that are currently and certainly will become more critical in the future. Data collection was carried out at the University of General Achmad Yani Yogyakarta. The transition from high school to university made Yogyakarta General Achmad Yani remodel all information systems and networks. The arrangement of information systems and networks that are good and in accordance with standards is nothing but to achieve the vision, mission and support for organizational integration of the University of General Achmad Yani Yogyakarta. The method used in this study is gap analysis and COBIT 5. COBIT 5 is one of the Best Practices on IT governance that describes the main role of information and technology to create "value." COBIT 5 separates the process of governance and management scope process The process of collecting data uses a structured interview method to the University of General Achmad Yani Yogyakarta.From data collection there were 2 IT Goals and 16 COBIT 5 domains namely EDM, APO, BAI, DSS and MEA. Gap analysis results in the EDM03, EDM04 process domain , APO01, APO07, APO10, APO12, BAI06, DSS03, DSS05 and MEA01 get the value of gap 1 and APO03, APO04, APO13, BAI09, BAI10, and DSS01 get the gap value 2